PEMANFAATAN TUMBUHAN OBAT SECARA TRADISIONAL OLEH MASYARAKAT DI DESA BANGUN SARI KECAMATAN TERIAK KABUPATEN BENGKAYANG - Dessy, .; Thavita, Gusti Eva; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2018)
West Borneo is well known for its wet tropical forests contain a wide variety of plants species that are traditionall used by society. The plants species used by the society are diverse like, undercoat plants, lianas, shrubs, and various other trees species and parts of plants that plant parts used also various such as roots, leaves, flowers, fruits, and seeds. This research conducted with snowball sampling method by chained interview on selected respondents. three were 37 respondents, interviewed selected from 223 households of Bangun Sari village of Teriak destrict of Bengkayang regency. the interviews were of conducted on households who know about medicinal plants such as heads of village, chairman of tribe, chairman of society, traditional herbalist and elder peoples. There were 43 plant species of 29 plant families, used by the society. the medicinal plants were found in forms of trees, herbs, shrubs, and lianas (13 species, 17 species, 11 species and 3 species, respeetively). most of the medicinal plants herb are used as single form (26 species) while 17 species are used in mixture. various plants parts are used such as leaves, rhizomes, roots, stems, fruits, saps. the were several methods used by the society in the preparation methods such as boiled, crushed, baked, squeezed, chewed and sliced, the herbs can administered in oral, smeared, eaten, and pasted.Keywords: Community, Medicinal, Of Plants, Utilization, Type